Acute laryngeal fracture in a male collegiate ice hockey athlete - Rossi, A. M.; Donovan, C. L.; Sharp, M. A. (International Journal of Athletic Therapy & Training, 2015)
Key Points: Acute laryngeal injuries account for 1 out of 42,528 emergency room visits. Only 10% of laryngeal injuries are related to athletics. There is a lack of knowledge regarding anterior laryngotracheal structure pathologies.